Sexual onset and contraceptive use among adolescents from poor neighbourhoods in Managua, Nicaragua. (April 2015) - Decat, Peter; De Meyer, Sara; Jaruseviciene, Lina; Orozco, Miguel; Ibarra, Marcia; Segura, Zoyla; Medina, Joel; Vega, Bernardo; Michielsen, Kristien; Temmerman, Marleen; Degomme, Olivier
Abstract Background and objectives The prevalence of teenage pregnancies in Nicaragua is the highest in Latin-America. This study aimed to gain insight into factors which determine the sexual behaviours concerned. Methods From July until August 2011, a door-to-door survey was conducted among adolescents living in randomly selected poor neighbourhoods of Managua. Logistic regression was used to analyse factors related to sexual onset and contraceptive use. Results Data from 2803 adolescents were analysed. Of the 475 and 299 sexually active boys and girls, 43% and 54%, respectively, reported contraceptive use. Sexual onset was positively related to increasing age, male sex, alcohol consumption and not living with the parents. Catholic boys and boys never feeling peer pressure to have sexual intercourse were more likely to report consistent condom use. Having a partner and feeling comfortable talking about sexuality with the partner were associated with hormonal contraception. Conclusions Our data identified associates of adolescents' sexual behaviour related to personal characteristics (sex and alcohol use), to the interaction with significant others (parents, partners, peers) and to the environment (housing condition, religion). We interpreted those associates within the context of the rapidly changing society and the recently implemented health system reform in Nicaragua.